Quality of teaching perceived by students of an Ecuadorian institution of higher education (LACCEI, 2024)
This research determines the student perception of the quality of teaching in an Ecuadorian institution of higher education. An instrument consisting of 22 items, adapted from Alvarado-Lagunas et al (2015), was used, which evaluates the perception that students have of the multiservices offered by the University in the teaching process, through variables associated with four dimensions: physical component, teaching staff, teaching ability and integral development. The instrument was applied to a sample of 175 students. The results indicate a good level of perceived quality of teaching in the institution and the factors that strengthen and weaken the system. It highlights the importance that students give to the physical facilities, equipment and staff that the institution has, the ability of teachers to provide education, among others. In addition, the results of this study suggest a significant relationship between the perceived quality and the degree of satisfaction with the teaching offered by the university.